Da Afghanistan Bank: quarterly economic & statistical bulletin, 20th June to 20th September 2004 - Da Afghanistan Bank, BRAC (© Da Afghanistan Bank, BRAC, 2016)
This bulletin is prepared by Macroeconomic & statistical unit of Da Afghanistan Bank, BRAC International.